Perancangan Sistem Absensi Khusus Karyawan WFH & Marketing Berbasis Web Dengan Fitur GPS ( Studi Kasus : Rumah Sakit Islam Asshobirin ) - Fajar Nurdiana Sunjaya; Gilang Budiman; Muhammad Hasby (CV. Multi Kreasi Media, 2022)
The marketing division is the initial mover of the sales division. In the marketing or marketing process, the task is to find information related to products and services offered by companies or public service institutions, product prices on the market, profiles of the targets to be achieved, and how and where to reach the target people who will become potential consumers of the product. Where they always work on a mobile basis and always move - move places. Employee attendance is an important factor for an agency or company engaged in various fields to achieve a goal, because this is related to the level of discipline and performance as well as payroll matters for each employee. The problem at the Asshobirin Islamic Hospital, South Tangerang City is the attendance system for marketing division employees who still use the manual attendance system, where employees must send messages via WhatsApp to make attendance reports, which will be manually recapitulated also by the admin, to be sent to the finance. Based on the weaknesses that exist in the attendance system (manual), the author wants to make a more modern employee attendance with web-based that can cover the weaknesses that exist in the old attendance system (manual), so that it can make it easier for employees, especially the marketing division to make attendance and make it easier for HRD to monitor the performance of its employees. Therefore, the author wants to make a